Sex-Based Differences in Gingival Inflammatory Responses to Porphyromonas gingivalis in Male and Female Rats - Dharmayanti, Agustin Wulan Suci; Setiawatie, Ernie Maduratna; Hendarto, Hendy (Trends in Sciences, 2025)
Periodontitis is defined as the inflammation of periodontal tissue. It is primarily caused by plaque bacteria, with Porphyromonas gingivalis being one of the most predominant bacteria. The inflammatory response to P. gingivalis varies by sex, as evidenced by higher serum titers in females than in males. This study aimed to compare the inflammatory responses in the gingiva of female and male rats following injection with P. gingivalis. The study was experimental laboratory using post-test control group design. Both male and female rats received injections of 2.109 cells/mL of P. gingivalis every 3 days over 19 days. The injections were into the distobuccal and distolingual gingival sulcus of the mandibular first molar. On the 19 days, tumor necrosis factor-alpha (TNF-α) levels of gingival fluid were measured using ELISA methods. Then, the rats were euthanized and removed the mandible. The number of leukocytes in the mandibular gingival tissue was assessed histologically using hematoxylin eosin staining. All of data were analyzed by Independent T-Test (p < 0.0 %). The findings revealed that the TNF-α levels in the gingival crevicular fluid of female rats (161.14 ng/mL) were significantly 1.5 times higher than male rats (109.57 ng/mL) after P. gingivalis injection (p < 0.05). The numbers of neutrophils and macrophages in female rats (neutrophils = 35.57 cells and macrophages = 13.71 cells) were significantly higher than those in male rats (neutrophils = 30.14 cells and macrophages = 8.43) (p < 0.05). However, the lymphocyte count was insignificantly comparable between sexes following injection (females = 22.24 cells and males = 22 cells) (p > 0.05). Sex differences might influence the immune response to P. gingivalis infection, with females exhibiting a stronger response characterized by increased leukocyte infiltration and TNF-α level than males. After injections of P. gingivalis, the inflammatory response observed in female rats was notably greater than that in male rats. HIGHLIGHTS Periodontitis is a chronic inflammatory disease that affects periodontal tissues, and Porphyromonas gingivalis is the main pathogen involved with this condition. The inflammatory response to gingivalis differs according to sex, regardless of smoking habit or existing systemic diseases. Female rats demonstrated a more intense inflammatory response than male rats following gingivalis infection. This study emphasizes the importance of recognizing sex differences in the biological mechanisms underlying the development of periodontal diseases. Women need to prioritize maintaining oral health, as they appear to be more susceptible than men to infections caused by periodontal pathogens. GRAPHICAL ABSTRACT